Community-based HPV self-collection versus visual inspection with acetic acid in Uganda: a cost-effectiveness analysis of the ASPIRE trial. Issue 6 (12th June 2018) - Mezei, Alex K; Pedersen, Heather N; Sy, Stephen; Regan, Catherine; Mitchell-Foster, Sheona M; Byamugisha, Josaphat; Sekikubo, Musa; Armstrong, Heather; Rawat, Angeli; Singer, Joel; Ogilvie, Gina S; Kim, Jane J; et al.
Abstract : Background: Cervical cancer is the leading cause of cancer death for women in Uganda, despite the potential for prevention through organised screening. Community-based self-collected human papillomavirus (HPV) testing has been proposed to reduce barriers to screening. Objective: Our objective was to evaluate the cost-effectiveness of the Advances in Screening and Prevention of Reproductive Cancers (ASPIRE) trial, conducted in Kisenyi, Uganda in April 2014 (n=500). The trial compared screening uptake and compliance with follow-up in two arms: (1) community-based (ie, home or workplace) self-collected HPV testing (facilitated by community health workers) with clinic-based visual inspection with acetic acid (VIA) triage of HPV-positive women ('HPV-VIA') and (2) clinic-based VIA ('VIA'). In both arms, VIA was performed at the local health unit by midwives with VIA-positive women receiving immediate treatment with cryotherapy. Design: We informed a Monte Carlo simulation model of HPV infection and cervical cancer with screening uptake, compliance and retrospective cost data from the ASPIRE trial; additional cost, test performance and treatment effectiveness data were drawn from observational studies. The model was used to assess the cost-effectiveness of each arm of ASPIRE, as well as an HPV screen-and-treat strategy ('HPV-ST') involving community-based self-collected HPV testing followed by treatment for all HPV-positive women at the clinic. Outcome measures: The primary outcomes were reductions in cervical cancer risk and incremental cost-effectiveness ratios (ICERs), expressed in dollars per year of life saved (YLS). Results: HPV-ST was the most effective and cost-effective screening strategy, reducing the lifetime absolute risk of cervical cancer from 4.2% (range: 3.8%–4.7%) to 3.5% (range: 3.2%–4%), 2.8% (range: 2.4%–3.1%) and 2.4% (range: 2.1%–2.7%) with ICERs of US130 (US110–US150) per YLS, US240 (US210–US280) per YLS, and US470 (US410–US550) per YLS when performed one, three and five times per lifetime, respectively. Findings were robust across sensitivity analyses, unless HPV costs were more than quadrupled. Conclusions: Community-based self-collected HPV testing followed by treatment for HPV-positive women has the potential to be an effective and cost-effective screening strategy.